Influence of K2CrO4 Doping on the Structural, Optical and Dielectric Properties of Polyvinyl Alcohol/K2CrO4 Composite Films. (11th February 2016) - Deshmukh, Kalim; Ahamed, M. Basheer; Deshmukh, Rajendra R.; Bhagat, Pundlik R.; Pasha, S. K. Khadheer; Bhagat, Aditya; Shirbhate, Rutwesh; Telare, Fastin; Lakhani, Chirag
ABSTRACT: Polyvinyl alcohol/potassium chromate (K2 CrO4 ) composite films were prepared by solution casting technique using distilled water as a solvent, and were further investigated using Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, X-ray diffraction, thermogravimetric analysis, optical microscopy, scanning electron microscopy, and dielectric measurements. Microscopic studies reveal that K2 CrO4 was homogenously mixed with polyvinyl alcohol matrix due to interfacial interaction between polyvinyl alcohol and K2 CrO4 . The composite films showed very high dielectric constant and relatively low dielectric loss. Hence, such composite materials with improved dielectric properties could be useful for fabrication of electrical charge storage device. GRAPHICAL ABSTRACT: